Vpliv odmora na mišični prirastek - Kolar, Jure (Šport (Ljubljana), 2016)
Rest is one of the most important variables of sport's training. Its main purpose is to stop catabolic phase and restore homeostasis. Determining optimal duration may play a crucial role in developing muscle hypertrophy. Usually intervals between 30 seconds and 3 minutes are employed, yet this range is relatively big and consequently different outcomes are expected, especially in combination with other variabiles. This article presents results of some studies examining differences between long and short interset rest intervals, impact of frequency as well as rest between training session and their effects on endocrine system and especially on hypertrophic response. In the end we provide some practical application for practicioners - athletes, physiotherapists and strength and conditioning coaches. We conclude that either long or short rest period induces a significant hypertrophy response. Latest studies indicade that hypertrophy stimulation is not a result of concentration changes of anabolic hormones. When programming training cycles, we must take into consideration different physiological recovery periods of different tissues.
Keywords: endokrine spremembe; frekvenca treniranja; frequency; hormonal changes; hypertrophy; interset rest interval; medserijski odmor; mišični prirastek; sport; šport